Depositional patterns of slowly plugging neck cutoffs from core analysis and estimates of bedload transport, White River, Arkansas. Issue 2 (3rd September 2021) - Richards, Derek; Konsoer, Kory; Langendoen, Eddy; Ursic, Mick; Constantine, JosÉ
Abstract: Meander cutoffs and oxbow lakes are very common features of fluvial landscapes that add complexity and diversity to floodplain alluvial architecture and riverine habitats. Following initial cutoff, sediment accumulates within the entrance and exit of the original bend forming plugs that eventually disconnect the abandoned bend from the main channel. While studies have examined the sedimentology of these plugs once they have fully disconnected from the abandoned bend, fewer studies have detailed the sedimentological processes occurring during the early stages following cutoff initiation. Furthermore, recent studies have highlighted the importance that planform geometry plays in the evolution of neck cutoffs. This study examines the spatial depositional patterns of two neck cutoffs on the White River in central Arkansas, USA, that remain hydrologically connected to the main channel, providing a unique opportunity to research sedimentological processes before disconnection of the abandoned bend. Sediment cores were collected in key locations of each cutoff, including the entrance and exit of the abandoned bends, abandoned bend apices, and newly developed cutoff bars in the downstream channel. The cores were logged and interpreted and grain‐size analyses were performed. In addition to sediment cores, repeat high‐resolution multibeam echo sounding surveys were conducted roughly four hours apart to estimate bedload transport rates and patterns of bedload routing through each cutoff. Results from this research are different from previous studies. Sediment core results show a pattern of deposition typically associated with lower diversion angle chute cutoffs instead of higher diversion angle neck cutoffs. Previous research has indicated that plugging of abandoned bends drives disconnection from the active channel; however, this research shows that disconnection is more associated with the prevention of sediment from being delivered to the abandoned bends due to flow being pulled away from the abandoned bends and the evolving channel morphology.